(untitled) (International Journal of Environmental Sciences, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder characterized by airflow limitation and persistent respiratory symptoms. Traditionally associated with malnutrition and low body mass (BMI), recent evidence suggests a growing prevalence of obesity in COPD patients, influencing disease severity, exacerbation, and quality of life. However, data on the relationship between obesity and COPD, particularly in Arab populations, remain limited. Aim of the study: To investigate the relationship between COPD and levels of obesity. Materials and methods: A cross-sectional study was conducted at Baghdad Teaching Hospital from June 2024 to June 2025, including 100 COPD patients. BMI was categorized as normal (<25 kg/m²), overweight (25–29.9 kg/m²), and obese (≥30 kg/m²). Dyspnea severity was assessed using the Medical Research Council (MRC) Dyspnea Scale, and quality of life was evaluated with the St. George’s Respiratory Questionnaire (SGRQ). COPD exacerbations, inhaled medication use, and comorbidities were analyzed. Statistical significance was set at p ≤ 0.05. Results: Obesity prevalence was 41%, and 75% of patients were overweight or obese. Higher BMI was significantly associated with increased dyspnea severity (p = 0.01), worse activity and impact scores (p < 0.05), and greater inhaled corticosteroid (ICS) use (p = 0.02). Lower BMI patients had significantly higher COPD exacerbation rates requiring prednisone and antibiotics (p = 0.02, p = 0.048). Conclusion: Obesity is highly prevalent in COPD patients and significantly influences dyspnea severity, quality of life, and ICS use. Lower BMI is associated with increased exacerbation frequency.